2008
DOI: 10.1182/blood-2007-11-123315
|View full text |Cite
|
Sign up to set email alerts
|

High expression of CD40 on B-cell precursor acute lymphoblastic leukemia blasts is an independent risk factor associated with improved survival and enhanced capacity to up-regulate the death receptor CD95

Abstract: CD40 and CD27, members of the tumor necrosis factor receptor (TNFR) family, are critical regulators of lymphocyte growth and differentiation. In B-cell precursor acute lymphoblastic leukemia (BCP-ALL), we prospectively assessed the impact of CD40 and CD27 on outcome in 121 children treated according to the CoALL06-97 protocol. Expression of both CD40 and CD27 was found to be significantly higher in low-than in high-risk patients as defined by standard clinical risk parameters such as age and white blood cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
1
6
0
2
Order By: Relevance
“…CD40 is the member of the tumor necrosis factor receptor (TNFR) family, are critical regulators of lymphocyte growth and differentiation. Troeger et al (2008) confirmed that the high expression of CD40 in BCP-ALL cells is an independent prognostic indicator, which indicates a better recurrencefree survival.…”
Section: The Functional Analysis Of the Selected Genessupporting
confidence: 54%
“…CD40 is the member of the tumor necrosis factor receptor (TNFR) family, are critical regulators of lymphocyte growth and differentiation. Troeger et al (2008) confirmed that the high expression of CD40 in BCP-ALL cells is an independent prognostic indicator, which indicates a better recurrencefree survival.…”
Section: The Functional Analysis Of the Selected Genessupporting
confidence: 54%
“…Findings on CD40 are consistent with the results published by Keidai et al, in which 51.9% of NSCLC tissue specimens [24] and 78% of lung cancer cell lines (14 of 18) expressed CD40 [25]. Furthermore, the expression of CD40 has been documented in many other carcinomas, such as melanomas [26], hepatocellular carcinomas [27] thyroid [28], bladder [29], colon [30], esophageal squamous cell [31], ovarian [32], gastric [33], cervical [34], breast and pancreatic cancer [35], as well as in the vast majority of hematological malignancies [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Dagmar Dilloo (Heinrich Heine Univ., Germany) presented approaches to enhance GVL in ALL. She has demonstrated that modulation of the ALL blast can also be used to augment GVL, and improved immunogenecity is seen after CD40 activation, via CD70 and CD80/86 upregulation, resulting in substantial T cell priming(51, 52). As blockade of CD70 prevents effector T cell expansion and reduces cytotoxicity, strategies facilitating upregulation of CD70 on antigen-presenting cells are critical for augmenting the quality of an anti-leukemic response against ALL.…”
Section: Augmenting Graft-versus-leukemia For Pediatric Hematologicalmentioning
confidence: 99%